Chemotherapy as Adjuvant Treatment for Intermediate-High Risk Early-Stage Endometrial Cancer: A Pilot Study. Issue 8 (1st October 2015) - Aloisi, Alessia; Plotti, Francesco; Scaletta, Giuseppe; Capriglione, Stella; Laraud, Federica; Miranda, Andrea; Montera, Roberto; De Cicco Nardone, Carlo; Terranova, Corrado; Angioli, Roberto
Abstract : Objective: This study aimed to assess primarily the role of chemotherapy as adjuvant treatment for International Federation of Gynecology and Obstetrics (FIGO) stage IA G3, IB G2-G3, and II endometrial cancer (EC) in terms of disease-free interval and overall survival, and secondarily, the rate of local and distant recurrence. Methods: The present prospective pilot study includes 68 patients with surgical staged EC who referred between 2007 and 2011 to the Division of Gynecologic Oncology at the University Campus Bio-Medico of Rome. All enrolled patients received adjuvant chemotherapy every 3 weeks according to the scheme carboplatin, dosed at an area under the curve of 6, and paclitaxel 175 mg/mq given every 3 weeks for at least 3 cycles. Results: The median number of chemotherapy cycles was 6 (range, 3–6 cycles). Chemotherapy was well tolerated. The 3-year overall survival was 92.8% and 91.6% for stages I and II, respectively. The 3-year disease-free interval was 91.8% and 83.3% for stages I and II, respectively. Of 68 patients, 7 (10.3%) relapsed: 5 patients with a FIGO stage I and 2 patients with FIGO stage II EC. Conclusions: Platinum-based chemotherapy is feasible and safe and it could be used in adjuvant setting for early-stage ECs. Although its effectiveness is comparable to radiotherapy, chemotherapy represents an excellent treatment option due to its systemic action. Further randomized studies will be needed to confirm our promising data.